2008
DOI: 10.1093/mp/ssn022
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Transcription Analysis Reveals a Close Correlation of Promoter INDEL Polymorphism and Heterotic Gene Expression in Rice Hybrids

Abstract: Heterosis, or hybrid vigor, refers to the phenomenon in which hybrid progeny of two inbred varieties exhibits enhanced growth or agronomic performance. Although a century-long history of research has generated several hypotheses regarding the genetic basis of heterosis, the molecular mechanisms underlying heterosis and heterotic gene expression remain elusive. Here, we report a genome-wide gene expression analysis of two heterotic crosses in rice, taking advantage of its fully sequenced genomes. Approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 44 publications
13
103
1
2
Order By: Relevance
“…For example, we found that the DG HP involved in the carbohydrate-metabolism pathway had a larger fraction of up-regulated genes than downregulated genes, similar to the recent studies (23,27). However, of the genes taking part in oxidative phosphorylation, there were more down-regulated genes identified in the hybrid than in the parental lines.…”
Section: Dg Are Candidates For Genes That Play An Important Role In Hsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, we found that the DG HP involved in the carbohydrate-metabolism pathway had a larger fraction of up-regulated genes than downregulated genes, similar to the recent studies (23,27). However, of the genes taking part in oxidative phosphorylation, there were more down-regulated genes identified in the hybrid than in the parental lines.…”
Section: Dg Are Candidates For Genes That Play An Important Role In Hsupporting
confidence: 88%
“…We indeed found that 187 TFs exhibited differential expression in the hybrid compared with either parent. It is quite a coincidence that a recent study using seedling tissue of 2 hybrid triads, based on the genomic sequence of 93-11 and nipponbare, also suggested that altered gene expression caused by interactions between transcription factors and the allelic promoter region in the hybrids was one plausible mechanism underlying heterosis in rice (23). Moreover, we noticed that among those differentially expressed TFs, the AP2-EREBP family-potential targets of miRNA (24)-is overrepresented.…”
Section: Discussion Complex Regulatory Mechanisms Probably Underlie Gmentioning
confidence: 58%
See 1 more Smart Citation
“…The two varieties of rice that we studied demonstrate significant heterosis, a phenomenon whereby matings by more distant plants, intra-or interspecies, result in offspring with superior agronomic traits, such as tiller number and dry weight (9,(23)(24)(25). Previous studies of heterosis have revealed possible mechanisms to account for the increased vigor, but the mechanisms that underlie this complex phenotype are still poorly understood, and the role of DNA methylation in heterosis is unclear (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 97%
“…Constraints on indel polymorphisms in intergenic regions have been demonstrated in Drosophila melanogaster (Ometto et al 2005). In rice, a study of genes displaying cis-regulatory differences in a heterotic F 1 cross were shown to be associated with indel variation and not single nucleotide polymorphism (Zhang et al 2008). Indel polymorphism may therefore alter cis-regulatory function more strongly than single nucleotide polymorphism.…”
Section: Resultsmentioning
confidence: 99%